The Dynamic Roles of Visfatin and Obestatin Serum Concentration in Pancreatic Beta Cells Dysfunction (HOMA-beta) and Insulin Resistance (HOMA-IR) in Centrally Obese Men - Bayu Winata Putera; Cynthia Retna Sartika; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2012)
BACKGROUND: Obesity is a major health problem in the world today. Obesity is closely associated with insulin resistance and type 2 diabetes. Epidemiological studies have shown that obese persons are in a state of insulin resistance, however, most of them do not progress to type 2 diabetes. This occurs because the beta cell function is still good enough for maintaining normal glucose level. Obestatin and visfatin are cytokines that are known to have a role in beta cell function. The aim of this study was to assess the relationship between visfatin and obestatin and Homeostasis Model Assessment of beta cell function (HOMA-β) and Homeostasis Model Assessment of insulin resistance (HOMA-IR).METHODS: This was a cross-sectional study involving 80 central obesity men with waist circumference >90 cm, age 30-65 years old. Visfatin and obestatin were measured by ELISA method. Beta pancreas cell dysfunction and insulin resistance were calculated by HOMA model.RESULTS: Our study showed a correlation between visfatin and HOMA-β (r=0.244 and p = 0.029) and visfatin with HOMA-IR (r=0.287 and p=0.001) and no correlation was found between obestatin with HOMA-β (r=0.010 and p=0.990) and obestatin with HOMA-IR (r=0.080 and p=0.480). We also found visfatin and obestatin concentrations were fluctuative depending on the measurements of the waist circumferences.CONCLUSIONS: High visfatin and low obestatin concentration were independently associated with increased beta pancreas cell dysfunction and insulin resistance.KEYWORDS: obesity. visfatin, obestatin, beta cell dysfunction (HOMA-β), insulin resistance (HOMA-IR)